2022
DOI: 10.1039/d2ce00210h
|View full text |Cite
|
Sign up to set email alerts
|

Dichlorine-containing chlorobismuthate(iii) supramolecular hybrid: structure and experimental studies of stability

Abstract: The chlorine-rich complex (Me4N)3{[Bi2Cl9](Cl2} (1) features dichlorine units incorporated into chlorometalate matrix via halogen bonding. 1 demonstrates relatively high thermal stability (release of Cl2 at >180°C).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…According to previous research, the structure of ((CH 3 ) 4 N) 3 Bi 2 Cl 9 exhibits high symmetry (hexagonal, space group = P 6 3 / mmc ), which comprises two isolated face-sharing Bi 2 Cl 9 3– octahedral anionic clusters encompassed by tetramethylammonium cations . Besides, there was no appearance of BiOCl, BiONO 3 , and/or metallic bismuth crystalline phases, confirming the purity of the product. , Interestingly, based on the position of the diffraction peak on the XRD pattern, the ((CH 3 ) 4 N) 3 Bi 2 Cl 9 structure in this study differs from the polychloro-chlorobismuthate structure, (Me 4 N) 3 {[Bi 2 Cl 9 ](Cl 2 )}, in the previous study, where Cl 2 fragments were incorporated into a chlorobismuthate matrix via halogen bonding . Moreover, high-purity ((CH 3 ) 4 N) 3 Bi 2 Cl 9 can be obtained when the DCM/DMF volume ratios are 10/50, 20/40, 30/30, and 40/20 (Figure B).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…According to previous research, the structure of ((CH 3 ) 4 N) 3 Bi 2 Cl 9 exhibits high symmetry (hexagonal, space group = P 6 3 / mmc ), which comprises two isolated face-sharing Bi 2 Cl 9 3– octahedral anionic clusters encompassed by tetramethylammonium cations . Besides, there was no appearance of BiOCl, BiONO 3 , and/or metallic bismuth crystalline phases, confirming the purity of the product. , Interestingly, based on the position of the diffraction peak on the XRD pattern, the ((CH 3 ) 4 N) 3 Bi 2 Cl 9 structure in this study differs from the polychloro-chlorobismuthate structure, (Me 4 N) 3 {[Bi 2 Cl 9 ](Cl 2 )}, in the previous study, where Cl 2 fragments were incorporated into a chlorobismuthate matrix via halogen bonding . Moreover, high-purity ((CH 3 ) 4 N) 3 Bi 2 Cl 9 can be obtained when the DCM/DMF volume ratios are 10/50, 20/40, 30/30, and 40/20 (Figure B).…”
Section: Resultsmentioning
confidence: 87%
“…28,29 Interestingly, based on the position of the diffraction peak on the XRD pattern, the ((CH 3 ) 4 N) 3 Bi 2 Cl 9 structure in this study differs from the polychloro-chlorobismuthate structure, (Me 4 N) 3 {[Bi 2 Cl 9 ](Cl 2 )}, in the previous study, where Cl 2 fragments were incorporated into a chlorobismuthate matrix via halogen bonding. 30 Moreover, high-purity ((CH 3 ) 4 N) 3 Bi 2 Cl 9 can be obtained when the DCM/DMF volume ratios are 10/50, 20/40, 30/30, and 40/ 20 (Figure 1B). However, the ((CH 3 ) 4 N) 3 Bi 2 Cl 9 formation occurs in the presence of the BiONO 3 and bismuth metal crystal phases when a DCM/DMF ratio of 50/10 was used.…”
Section: Characterization Of Bismuth Halide Perovskitementioning
confidence: 97%
“…Polyhalides are a subject of intensive studies and these species found various applications as electrolytes for batteries and also for dye-sensitized solar cells, , mild selective oxidants for organic synthesis, and synthons for the construction of metal–organic frameworks . Metal polyhalide complexes, namely species bearing metal–halogen coordination or semicoordination bonds, have been attracting increasing interest for the past decade; the recent review summarizes advances in the chemistry of metal polyhalides, indicating, in particular, that polyiodides are substantially more abundant than polybromides, while the number of studied polychlorides (for the relevant literature, see refs ) is rather small.…”
Section: Resultsmentioning
confidence: 99%